Functional diversity of the lepidopteran ATP-binding cassette transporters - Barve, Pranoti R.; Tellis, Meenakshi B.; Barvkar, Vitthal T.; Joshi, Rakesh S.; Giri, Ashok P.; Kotkar, Hemlata M. (Journal of Molecular Evolution, 2022)
The ATP-binding cassette (ABC) transporter gene family is ubiquitous in the living world. ABC proteins bind and hydrolyze ATP to transport a myriad of molecules across various lipid-containing membrane systems. They have been studied well in plants for transport of a variety of compounds and particularly, in vertebrates due to their direct involvement in resistance mechanisms against several toxic molecules/metabolites. ABC transporters in insects are found within large multigene families involved in the efflux of chemical insecticides and toxic/undesired metabolites originating from food and endogenous metabolism. This review deals with ABC transporter subfamilies of few agronomically important Lepidopteran pests. The transcriptional dynamics and regulation of ABC transporters during insect development emphasizes their functional diversity against insecticides, Cry toxins, and plant specialized metabolites. To generate insights about molecular function and physiological roles of ABCs, functional and structural characterization is necessary. Also, expansion and divergence of ABC transporter gene subfamilies in Lepidopteran insects needs more systematic investigation. We anticipate that newer methods of insect control in agriculture can benefit from an understanding of ABC transporter interactions with a vast range of natural specialized molecules and synthetic compounds.
Keywords: ABC transporters; Bt; insecticide resistance; Lepidoptera; Plant metabolites